A neutron reflectivity study of the adsorption of aerosol-OT on self-assembled monolayers on silicon - Fragneto, G; Li, Z; Thomas, R; Rennie, A; Penfold, J (1996)
The structure and composition of layers of the anionic surfactant sodium bis-(2-ethyl-1-hexanol) sulphosuccinate (AOT) adsorbed from aqueous solution onto self-assembled monolayers of octadecyltrichlorosilane (OTS) on silicon oxide have been determined in situ using specular neutron reflection. At its critical micelle concentration (cmc) AOT forms a monolayer with an area per molecule of 80 ± 5 Å2 and a thickness of 15 ± 2 Å. These values are similar to those of the monolayer formed at the air/water interface at the cmc. Separate isotopic labeling of two parts of the AOT surfactant shows that the molecule is oriented with the ethyl hexanol chains toward the hydrophobic OTS surface and that there is some penetration of the OTS layer by the chains. The adsorption of AOT is found to persist at lower concentrations than the nonionic surfactant tetraethylene glycol monododecyl ether (C12E4) over the concentration range cmc/100 to cmc.